Sedimentary Nutrient Dynamics in Homestead Fishpond Systems from a Subtropical Coastal Area - Anu Rani Karmakar; Md. Akram Ullah; Md. Monjurul Hasan; Liza Akter; Md. Milon Sarker; Takaomi Arai; Mohammad Nurul Azim Sikder; Mohammed Fahad Albeshr; Mohammad Belal Hossain (Agriculture, 2022)
Homestead ponds are small seasonal ponds that are rarely utilized for fish farming. Culturing fish in these small ponds can boost household fish consumption and cash inflow. The availability of nutrients in the water and sediment, however, plays a significant role in the pond’s natural productivity. This study was conducted to assess nutrient contents and some key physical parameters in the bottom sediments of 30 homestead ponds from the central coast along the Northern Bay of Bengal. Analyses of results showed the average values (±SD) of temperature, pH, electrical conductivity, organic matter (OM), organic carbon (°C), nitrogen (N), phosphorus (P) and sulphur (S) were 17.8 ± 1.12 °C, 7.29 ± 0.11, 0.41 ± 0.09 mS/cm, 29,615.48 ± 10,528.9 mg kg−1, 11,958 ± 6107 mg kg−1, 1030.6 ± 252 mg kg−1, 17.1 ± 13.5 mg kg−1 and 32.6 ± 19.7 mg kg−1 during winter and 27.2 ± 1.81 °C, 6.73 ± 0.12, 0.38 ± 0.17 mS/cm, 19,100.01 ± 13,739.07 mg kg−1, 11,079 ± 7969 mg kg−1, 955 ± 229.4 mg kg−1, 26.6 ± 20.2 mg kg−1 and 23.4 ± 15.9 mg kg−1 during pre-monsoon, respectively. One-way ANOVA revealed no significant differences in the mean value of sediment quality parameters among the selected ponds (p > 0.05) except for phosphorus in the winter season (p < 0.05). The sediment quality variables were found to be in the suitable range for fish culture. Pearson’s correlation coefficient values (r) showed that only organic carbon and nitrogen had a strong significant correlation with organic matter (p < 0.05). Based on Cluster Analysis (CA), two major associations among the nutrients were attained at a 15% similarity level: C, OM, and N in one cluster and P and S in another. The findings showed that the parameters were within the preferable range for aquaculture, and the homestead ponds are average productive ponds.